Analyses of Helsinki 2012 European Athletics Championships injury and illness surveillance to discuss elite athletes risk factors - Edouard, P.; Depiesse, F.; Branco, P.; Alonso, J.-M. (Clinical Journal of Sport Medicine, 2014)
Objective: To further analyze newly incurred injuries and illnesses (I&Is) during Athletics International Championships to discuss risk factors. Design: Prospective recording of newly occurred injuries and illnesses. Setting: The 2012 European Athletics (EA) Championships in Helsinki, Finland. Participants: National team and local organizing committee physicians and physiotherapists and 1342 registered athletes. Main Outcome Measures: Incidence and characteristics of new injuries and illnesses. Results: Ninety-three percent of athletes were covered by medical teams, with a response rate of 91%. One hundred thirty-three injuries were reported (incidence of 98.4 injuries per 1000 registered athletes). Sixty-two injuries (47%) resulted in time loss from sport. The most common diagnosis was hamstring strain (11.4% of injuries and 21% of time-loss injuries). Injury risk was higher in males and increased with age. The highest incidences of injuries were found in combined events and middle- and long-distance events. Twenty-seven illnesses were reported (4.0 illnesses per 1000 athlete days). The most common diagnoses were upper respiratory tract infection (33.3%) and gastroenteritis/diarrhea (25.9%). Conclusions: During outdoor EA Championships, injury and illness incidences were slightly lower and injury characteristics were comparable with those during outdoor World Athletics Championships. During elite athletics Championships, gender (male), age (older than 30 years), finals, and some events (combined events and middle- and long-distance races) seem to be injury risk factors. Illness risk factors remain unclear. As in previous recommendations, preventive interventions should focus on overuse injuries, hamstring strains, and adequate rehabilitation of previous injuries, decreasing risk of infectious diseases transmission, appropriate event scheduling, sports clothes, and heat acclimatization.